Problems of the coal sector and suggested solutions - Druzhynina, Olena (My University, 2014)
The aim of this thesis is to analyze negative social, economic and environmental impacts of coal mining and combustion. Special attention is given to the problem of greenhouse gas emissions and emissions reduction policies and technologies. Метою даної роботи є аналіз негативних соціальних, економічних та екологічних наслідків видобутку вугілля і спалювання. Особлива увага приділяється проблемі викидів парникових газів і політики скорочення викидів і технологій.
Keywords: greenhouse gases; coal; вугілля; парникові гази